2015
DOI: 10.1589/rika.30.839
|View full text |Cite
|
Sign up to set email alerts
|

Association of Energy Intake and Walking Ability in Vertebral Compression Fracture

Abstract: [Purpose] To clarify vertebral compression fracture (VCF) patients' dietary status, and to investigate the association of their energy intake and walking ability, an outcome measure of rehabilitation.[Subjects] Thirtyone VCF patients who could walk independently prior to VCF. [Methods] Their energy intake ratio (energy intake/ energy consumption) was assessed over 7 days of hospital admission. Patients with an energy intake ratio ≥1.0 were assigned to the sufficient (SUF) group, and those with a ratio <1.0 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…For example, previous studies reported that nutritional states were related to functional outcomes in elderly patients 3 ) and those with various diseases, such as stroke 4) , Parkinson's disease 5 ) , distal radius fracture 6) , and pneumonia 7) . Similarly, it has been reported that nutritional status is associated with improvement in activities of daily living (ADL) and gait ability in patients with hip and vertebral compression fractures [8][9][10][11][12] . Although there are some reports that nutritional interventions have not had significant impacts on long-term outcomes after hip fractures 13,14) , other studies have shown that nutritional inter-ventions are effective for improving ADL and gait ability in patients with hip fractures 8) .…”
mentioning
confidence: 94%
“…For example, previous studies reported that nutritional states were related to functional outcomes in elderly patients 3 ) and those with various diseases, such as stroke 4) , Parkinson's disease 5 ) , distal radius fracture 6) , and pneumonia 7) . Similarly, it has been reported that nutritional status is associated with improvement in activities of daily living (ADL) and gait ability in patients with hip and vertebral compression fractures [8][9][10][11][12] . Although there are some reports that nutritional interventions have not had significant impacts on long-term outcomes after hip fractures 13,14) , other studies have shown that nutritional inter-ventions are effective for improving ADL and gait ability in patients with hip fractures 8) .…”
mentioning
confidence: 94%